The Effects of Light and Height of Building in Attracting Paederus fuscipes Curtis to Disperse towards Human Residential Areas - Sufian Maryam; Nik Fadzly; Wan Fatma Zuharah (Tropical Life Sciences Research, 2016)
Paederus fuscipes Curtis is a nocturnal insect. The attractiveness of artificial light sources from residential premises eventually causes the risk of severe dermatitis effect, once Paederus is in contact with human skin. The objective of this study is to investigate whether the light and height factors of residential buildings and its’ association to rice cultivation phases are primary reasons for P. fuscipes’s mass dispersal into human residential areas. The study site was located in residential premises that were built adjacent to rice field areas (? 32–60 m and 164 m) north of the rice field located in Teluk Air Tawar, mainland of Pulau Pinang. Overall, both light sources and rice cultivation phases caused a significant effect for P. fuscipes beetles dispersal flight to invade human settlements. More P. fuscipes were captured near the bright light source with the highest number of beetles found during harvesting stage. Whereas, significantly higher number of P. fuscipes were captured at level 2 and 3 compared to ground and level 1 of the apartment building and P. fuscipes was also found significantly affected by the rice cultivation phases at different elevation levels. This indicates that bright light sources and higher elevation levels are the main factors in attracting P. fuscipes beetles to disperse and causes infestations in residential areas. This finding could create awareness among the public on P. fuscipes dispersal pattern.